Capital Budgeting jako podstawa decyzyjna w analizie rachunku inwestycyjnego - Siewiera, Agnieszka (Capital Budgeting as a Basis of Investment Appraisal, 2006)
The aim of the paper is to present the meaning of investment appraisal process from the point of view of company objectives. The most important factors, stages and criteria used in capital budgeting were depicted. The main emphasis was put on the essence of capital budgeting taking into account some methodological considerations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 371-379